THE EFFECT OF VARYING PROPYLENE GLYCOL CONCENTRATIONS ON THE PHYSICAL AND CHEMICAL STABILITY OF AVERRHOA BILIMBI LEAF EXTRACT CREAM FORMULATION - I Gusti Ayu Nadia Prasta Unique (Buletin Veteriner Udayana, 2026)
Creams are one of the most widely used topical formulations for the treatment of acne because they are easy to apply, comfortable to use, and easy to wash off. Averrhoa bilimbi leaves are known to contain flavonoids and tannins that have potential as antibacterial agents against acne-causing bacteria; however, natural-based formulations generally have poor physical stability. This study aims to determine the effect of varying propylene glycol concentrations on the physical and chemical stability of Averrhoa bilimbi leaf extract cream formulations and to identify the most optimal propylene glycol concentration. This study is an experimental study using three formulations with varying propylene glycol concentrations, namely 8%, 10%, and 12%. Physical properties were evaluated through organoleptic testing, homogeneity, pH, spreadability, adhesion, and stability testing using the freeze-thaw cycling test method for 3 cycles or 6 days. The results showed that all formulations met the requirements for organoleptic testing, homogeneity, and pH. However, only formulation 3 with a 12% propylene glycol concentration met all physical evaluation parameters, including spreadability and adhesion. Formula 3 showed a spreadability value of 5.49 cm before the stability test and 6.10 cm after the stability test, as well as an adhesion value of 4.61 seconds before the stability test and 4.35 seconds after the stability test. Based on the research results, it can be concluded that variations in propylene glycol concentration affect the physical stability of the Averrhoa bilimbi leaf extract cream formulation, and a 12% propylene glycol concentration is the most optimal formula.